Response to Fuson, Clements, and Sarama Commentary on Litkowski, Duncan, Logan, and Purpura (2020) - David J. Purpura; Ellen C. Litkowski; Robert J. Duncan; Jessica A. R. Logan (SAGE Publishing, 2021)
In response to Fuson et al.'s commentary on Litkowski et al. (2020), we clarify and expand on three areas: (1) the need for prekindergarten standards, (2) the value in developmental survey work, and (3) the importance of understanding curriculum translation and uptake. Specifically, we note that standards need to be appropriate for grade-level and it is time for more aligned prekindergarten standards. Developmental survey work is critical for ensuring that standards and expectations are accurate and adjusted to meet current needs and can be used address equity issues in instruction. Furthermore, we agree that intervention and curriculum work are needed, but there should be explicit emphasis on enhancing uptake and use of high-quality instruction. Ultimately, we need a system of assessment and instruction that is continually updated and improved, that integrates and modifies new evidence over time to ensure that we are striving for-and attaining-the best results for young children.